Determinants of crime : an empirical study in Malaysian Borneo - Teo, Shu Hui (Universiti Malaysia Sarawak (UNIMAS), 2015)
The worsening crime situation has been a major concern for people and it is becoming a constant source of discussion and debate among politicians and the general public. Television news in Malaysia frequently conveys the accounts of crimes committed by both locals and foreigners. Likewise, newspapers, repeatedly show that the crime rate is spiraling alarmingly. With this barrage of media reporting, society is now anxious and fearful as to what the future will hold for the economy of Sarawak and Sabah. The aim of this study is to examine whether real GDP per capita, inflation, population density and unemployment will have any effect on the total crime, property crime and violent crime in Sarawak and Sabah. The results of this study show that in Sarawak and Sabah, there is no existence of cointegrating vector which thus indicates no longrun relationship between crime (total crime, property crime and violent crime) and real GDP per capita, population density and inflation. However, there does exist one cointegrating vector between violent crime and unemployment for Sarawak and crime (total crime, property crime and violent crime) and unemployment for Sabah. The Granger causality test results show bi-directional relationship where total crime and property crime Granger cause unemployment and vice versa, while violent crime and unemployment only show uni-directional relationship in Sarawak. On the other hand, unemployment Granger causes total crime, property crime and violent crime in Sabah. Therefore, it can be concluded that not all the variables have a relationship in the short-run. The most significant measure that can curb the problems is to generate economic growth. With more economic opportunities, employment can be increased as more businesses and investment will flow into the country, thus creating greater job opportunities. Besides that, parents and teachers have the important roles to instill good moral values in the young generation. As what is often said by the elders, “spare the rod, spoil the child”. Therefore, education plays a key role in building up highly disciplined citizens. Lastly, the police needs to play their role by consistently enforcing laws and regulations to maintain peace in the country.